RHEOLOGICAL MODELING OF CASSAVA (Manihot esculenta</> CRANZ) STARCHES AND FLOURS DURING EXTRUSION PROCESS - SANDOVAL A., Angélica P.; FARHAT, Imad; FERNÁNDEZ Q., Alejandro (Vitae, 2009)
Rheological modeling of cassava flours and starches during an extrusion process was made in order to predict the effect of shear rate, temperature and water contents on viscosity. Experimentation was made on a high pressure twin bore capillary rheometer (Rosand RH-7) and viscosity data were adjusted to the Harper rheological model. All materials presented a characteristic shear thinning behaviour, but starch viscosity was more sensitive to changes of the processing conditions such as temperature and water contents, whereas flour viscosity was influenced by fiber and protein which interfered with starch gelatinization.